Pengaruh Keberadaan Bandar Udara Kelas III Seko Luwu Utara Terhadap Index Pencemaran Air - M.Ichsan Ali; Muh. Rais Abidin (Universitas Negeri Gorontalo, 2020)
The airport is one of the best transportation systems capable of moving people quickly as fast economic growth is followed by rapid population growth. Also, rapid population growth leads to massive exploitation of natural resources which causes environmental degradation such as illegal logging. Seko Airport, located in North Luwu is indicated to have caused environmental pollution, especially in watersheds. Therefore, this study aims to identify water pollution through physical and chemical parameters. Data were analyzed using the pollution index method to find the index value. The results showed that the waters around Seko Airport had an index value of 0.78 which was categorized as not polluted. This happens because the airport has a good water treatment system. Besides, there are strict regulations and guidance for all visitors and the local community to not throw rubbish into water bodies.